Consumo de oxigênio no domínio de intensidade severo durante teste incremental e retangular - de Moura, Rodrigo Ferreira [UNESP]; Kokubun, Eduardo [UNESP] (FapUNIFESP (SciELO), 2008)
Incremental tests are commonly used to predict metabolic responses during square-wave mode exercises. However, in some cases the predicted and observed results may be not similar. Main objective: To verify the hypothesis that, at certain intensities in the severe domain, VO2 determined during the incremental test is lower than that observed at these workloads using the square-wave test. Methodological proceedings: Eight physically active males (21.5 ± 4 years, 73.7 ± 5.3 kg and 180.8 ± 4.1 cm) performed: 1) an incremental test on cycle ergometer to determine the VO2 of the intensities (VO2INC); 2) a square-wave test at three severe intensities (Light (L), Medium (M) and Heavy (H) to determine the critical power (CP) and to compare the VO2 (VO2RET) observed with the VO2INC;3) a square-wave test at CP intensity to compare the time response of VO2 with P, M and L, at four different sample times. Results: The VO2INCat L intensity underestimated the VO2RET(3.2 ± 0.5 vs. 3.8 ± 0.6 l.min-1). No differences were observed at the other intensities (M: 3.5 ± 0.5 vs. 3.6 ± 0.5 l.min-1; H: 3.7 ± 0.5 vs. 3.4 ± 0.6 l.min-1; CP: 2.7 ± 0.5 vs. 3.0 ± 0.6 l.min-1). The VO2 at CP was lower at all times, exhibited a steady state and did not achieve VO2max. Initially, at L intensity, the VO2 was smaller than its pairs. However, at the last sample time, it achieved VO2max and became equal to the other severe intensities. Conclusion: The incremental test underestimates the VO2 observed at lighter intensities within the severe domain.
Oxygen consumption in the severe exercise intensity domain during incremental and square-wave test modes
Keywords: Constant power; Oxygen uptake; Progressive test; Severe domain